Compensation of Dynamic Fixation Systems in the Quality of Reduction of Distal Tibiofibular Joint in Acute Syndesmotic Complex Injuries: A CT-Based Analysis. (November 2022) - Spindler, Fabian T.; Gaube, Federico P.; Böcker, Wolfgang; Polzer, Hans; Baumbach, Sebastian F.
Background: There is an ongoing discussion on how to best stabilize syndesmotic injuries. Previous studies have indicated a better quality of reduction of the distal tibiofibular joint (DTFJ) for the suture button systems compared to syndesmotic screw fixation. Still, the reason for this superiority remains unclear. The aims of this retrospective study were to (1) analyze the deviation of the tibial and fibular drilling tunnels of the suture button system and (2) to compare these to the quality of reduction of the DTFJ assessed on bilateral postoperative CT images. Methods: Included were all adult patients who underwent syndesmotic stabilization for an acute injury using a suture button system, with postoperative, bilateral CT imaging over a 10-year period. A total of 147 patients were eligible. Based on individually reconstructed axial CT slices, the postoperative quality of reduction of the DTFJs was rated on bilateral CT images. Furthermore, the rotation and translation of the suture button drilling tunnels were analyzed. Based on these measurements, the intraoperative reduction of the DTFJ was recalculated and again rated. Using these values, the correction potential of suture button systems on the reduction of the DTFJ was analyzed. Results: (1) The drilling tunnel deviated considerably for both rotation |2.3±2.1 degrees| (range: |0.0-13.1 degrees|) and translation |0.9±0.8 mm| (range: |0-4.3 mm|). Based on the deviation of the drilling tunnels in fibula and tibia, the calculated intraoperative reduction of the DTFJ was classified as malreduced in 35.4%. (2) The DTFJ was postoperatively identified as malreduced in 17% of patients. Overall, the suture button system tended to compensate toward a more anatomical reduction both in the axial and sagittal plane. Conclusion: A suture button system postoperatively deviates and apparently has the capacity to compensate for intraoperative malreduction. Analysis of the drilling tunnels revealed that the use of a rigid fixation system would have doubled the postoperative malreduction rate.